Ontogenetic development and sexual dimorphism of franciscana dolphin skull: A 3D geometric morphometric approach - del Castillo, Daniela Laura (2014)
The aim of this work was to study the postnatal ontogenetic development of Pontoporia blainvillei skull, identifying major changes on shape, and relating them to relevant factors in the life history of the species. We analyzed a complete ontogenetic series (73♂, 83♀) with three-dimensional geometric morphometric techniques. Immature dolphins showed a very well-developed braincase and a poorly developed rostrum, and the principal postnatal changes affected the rostrum and the temporal fossa, both structures implied functionally to the feeding apparatus, thus suggesting a specialized mode for catch fast prey in P. blainvillei. Osseous elements associated with sound production were already well developed on immature dolphins, suggesting the importance of this apparatus since the beginning of postnatal life. Sexual dimorphism was detected on both shape and size variables. Females were bigger than males, in accordance with previous studies. Shape differences between sexes were found on the posterior part of premaxillaries and external bony nares (P<0.01), suggesting that this sexual dimorphism is related to differences on vocalization capabilities.